Magma Evolution and Petrogenesis of Volcanic Rocks at Kaba Volcano, Bengkulu - Muhammad Eval Juni Wijaya; Sakilla Gia Mentari; Chris John Sitinjak; Theo Sampit Mo Rizky Bantjin (Universitas Negeri Gorontalo, 2026)
Mount Kaba is an active stratovolcano in the Bengkulu Province, Indonesia, characterized by explosive eruptions and multiple eruptive centers, reflecting a complex magmatic system. This study investigated the magma evolution and petrogenesis of volcanic rocks from the northern sector of Mount Kaba using integrated petrographic and whole-rock geochemical analyses. Fifteen representative lava and pyroclastic rock samples were analyzed for major elements using inductively coupled plasma–optical emission spectrometry (ICP-OES), while trace and rare earth elements (REE) were determined using inductively coupled plasma–mass spectrometry (ICP-MS). The analyzed rocks ranged from basalt to andesite, with SiO₂ contents between 44.41 and 63.41 wt%, and generally low loss-on-ignition values, indicating relatively fresh compositions. Petrographic observations revealed porphyritic, vesicular, subophytic, intersertal, zoning, sieve, and reaction rim textures, suggesting dynamic magma chamber processes and disequilibrium crystallization. Geochemical classification based on total alkali silica (TAS) and K₂O–SiO₂ diagrams indicates alkaline, calc-alkaline, and high-K calc-alkaline affinities, which can be grouped into two magma series: the Danau Mas Group and the Kaba Group. Major and trace element variation diagrams show decreasing MgO, Fe₂O₃, and CaO with increasing SiO₂, accompanied by enrichment of alkali and incompatible elements, indicating magma differentiation dominated by fractional crystallization. Primitive mantle- and chondrite-normalized patterns display enrichment of large ion lithophile elements (LILE) and light rare earth elements (LREE), together with depletion of high field strength elements (HFSE), suggesting derivation from a mantle source modified by subduction-related fluids. Overall, the results indicate that Mount Kaba magmatism evolved through mantle wedge melting, followed by crustal-level magma differentiation within a subduction-related volcanic arc system.